2012
DOI: 10.1245/s10434-012-2654-2
|View full text |Cite
|
Sign up to set email alerts
|

Multifocality and Total Tumor Diameter Predict Central Neck Lymph Node Metastases in Papillary Thyroid Microcarcinoma

Abstract: Multifocal PTMC with TTD > 1 cm has a similar risk of LNM as a clinical papillary cancer. Routine central neck dissection is recommended in this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
105
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 36 publications
13
105
4
2
Order By: Relevance
“…Therefore, the TTD, which was defined as the sum of the maximal diameter of each lesion, was calculated. Univariate and multivariate analyses revealed that TTD >10 mm was statistically significantly associated with CLNM in the present study, which was similar to the findings of a previous study by Zhao et al (31). In the present study, tumor bilaterality was not an independent predictive factor for CLNM, although this has been demonstrated to be significantly associated with CLNM in a previous study (24).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the TTD, which was defined as the sum of the maximal diameter of each lesion, was calculated. Univariate and multivariate analyses revealed that TTD >10 mm was statistically significantly associated with CLNM in the present study, which was similar to the findings of a previous study by Zhao et al (31). In the present study, tumor bilaterality was not an independent predictive factor for CLNM, although this has been demonstrated to be significantly associated with CLNM in a previous study (24).…”
Section: Discussionsupporting
confidence: 91%
“…Although these differences were too small to be significant, they suggest that multifocality might represent the tumor burden and predict more aggressive behavior during disease progression. An interesting finding of the current study was that an increasing number of tumor foci was associated with a younger age at diagnosis in PTC, in contrast to previous reports that advanced age is a prognostic factor for poor prognosis in PTC [12][13][14][15]. Younger age may indicate greater risk for the evolution of biological aggressiveness, such as multifocality; we previously reported that younger age is significantly associated with cervical LNM in PTC.…”
Section: Discussioncontrasting
confidence: 83%
“…Studies have shown multifocal PTC may be related to clonal selection from a preneoplastic field and spread throughout the thyroid gland (Jovanovic et al, 2010;Mazeh et al, 2011), which may be linked to central compartment LNM (Zhao et al, 2013). Kim et al (2013) also demonstrated that multifocaltiy is an independent predictive factor for central LNM.…”
Section: Discussionmentioning
confidence: 99%